NON PERFORMING FINANCING, PROFIT SHARING FINANCING, BUYING AND SELLING FINANCING, LEASING FINANCING AND THEIR INFLUENCE ON RETURN ON ASSETS (Case Study of PT. Bank Muamalat Indonesia Period 2012-2019) - Bayu Segarahin; Hartomi Maulana (Islamic Business and Management Journal, 2020)
This study aims to examine the influence of Non Performing Financing (NPF), Profit Sharing Financing (PSF), Buying and Selling Financing (BSF) and Leasing Financing (LF) on Return On Assets at PT. Bank Muamalat Indonesia for the period of 2012-2019. The research method used is quantitative approach. The data in this study were obtained from PT. Bank Muamalat Indonesia Quarterly Financial (Maulana et al., 2019) Statement between 2012 quarter I and 2019 quarter III, retrieved from Financial Service Authority or Otoritas Jasa Keuangan (OJK) website. The analysis technique used in this research is multiple linear regression analysis which aims to determine the influence of independent variables on dependent variable employed in this study. The result shows that NPF and BSF have negatively influence on ROA, while PSF has positively influence. However, LF has no influence on ROA statistically.